An injectable hyaluronic acid/lithium calcium silicate soft tissue filler with vascularization and collagen regeneration - Jinzhou Huang; Jianmin Xue; Jimin Huang; Xinxin Zhang; Hongjian Zhang; Lin Du; Dong Zhai; Zhiguang Huan; Yufang Zhu; Chengtie Wu (Bioactive Materials)
The significance of collagen and vascular in skin augmentation have been recognized in recent years. However, current skin tissue fillers, e.g. hyaluronic acid (HA) or HA-based hydrogel, fail to meet the perfect augmentation requirements due to their inadequate long-term support effect and the lack of tissue-inducing activity. Herein, an injectable skin filler containing hyaluronic acid (HA) hydrogel and lithium calcium silicate (LCS, Li2Ca4Si4O13) bioceramic microspheres was developed for skin tissue fillers, owing to the excellent biological function of silicate bioceramics. The HA-LCS fillers could be easily injected through a tiny standard medical needle (27 G) with force of less than 36 N, and showed good biocompatibility both in vitro and in vivo. Furthermore, the bioactive ions released from HA-LCS fillers significantly enhanced the expression of vascularization-related genes and collagen-related genes. Importantly, the HA-LCS fillers not only stimulated the regeneration of mature blood vessels, but also promoted collagen secretion in dermal skin and filling area. This study not only presented an injectable filler with enhanced regeneration of blood vessels and collagen, but also provided a new strategy for developing tissue-induced fillers based on bioactive components of silicate bioceramics.